Signal initiation by preTCR and TCRγδ in early thymocyte progenitors does not require extracellular domains previously implicated in receptor oligomerization - Mahtani-Patching, Juliet (2011)
Whether thymocytes adopt an αβ or a γδ T cell fate in the thymus is determined at a checkpoint (β-selection) by the relatively weak or strong signals that are delivered by either the pre-T cell receptor (preTCR) or the γδ TCR, respectively. However, how these signals are initiated, and how different signal strengths are generated, remains unclear. Although binding of thymic agonist ligand would predict strong signaling, the preTCR and TCRγδ appear to be capable of ligand-independent signaling. Some reports have suggested that receptor oligomerization, which is thought to be mediated by either the immunoglobulin (Ig)-like domain of the preTCR α-chain (pTα) or the variable domain of TCRδ, is a unifying mechanism that initiates signaling in early CD4(−) CD8(−) double negative (DN) thymocyte progenitors. Here, we demonstrate that the extracellular regions of pTα and TCRd that were implicated in mediating receptor oligomerization were not required for signal initiation from the preTCR or TCRγδ. Indeed, a truncated TCRγδ that lacked all of its extracellular Ig-like domains still formed a signaling-competent TCR that drove cells through the β-selection checkpoint. These observations suggest that signal initiation in DN thymocytes is simply a consequence of the surface-pairing of TCR chains, with signal strength being a function of the abundances of surface TCR. Thus, processes that regulate the surface abundances of TCR complexes in DN cells, such as oligomerization-induced endocytosis, would be predicted to have a major influence in determining whether cells adopt an αβ versus γδ T cell fate.